Reflectance confocal microscopy and dermoscopy for in vivo, non-invasive skin imaging of superficial basal cell carcinoma - GHITA, MIHAELA A. (Oncol Lett, 2016)
Superficial basal cell carcinoma (sBCC) is the second most frequent histological type of basal cell carcinoma (BCC), usually requiring a skin biopsy to confirm the diagnosis. It usually appears on the upper trunk and shoulders as erythematous and squamous lesions. Although it has a slow growth and seldom metastasizes, early diagnosis and management are of crucial importance in preventing local invasion and subsequent disfigurement. Dermoscopy is nowadays an indispensable tool for the dermatologist when evaluating skin tumors. Reflectance confocal microscopy (RCM) is a novel imaging technique that allows the non-invasive, in vivo quasi-microscopic morphological and dynamic assessment of superficial skin tumors. Moreover, it offers the advantage of performing infinite repeatable determinations to monitor disease progression and non-surgical treatment for sBCC. Herein, we present three lesions of sBCC evaluated using in vivo and non-invasive imaging techniques, emphasizing the usefulness of combining RCM with dermoscopy for increasing the diagnostic accuracy of sBCC.